Instari, Tuutti, Kääntis. Suomalaisen kääntäjänkoulutuksen historiaa - Ivaska, Laura; Paloposki, Outi; Salmi, Leena (Finland, 2025)
The 20th century saw the birth of translator training in different parts of the world. In Finland, the first translator and interpreter training institutions, the so-called Language Institutes, were established in 1966. Today, many institutions offer interpreter and translator training in Finland, including sign language interpreting, among other subjects. Four translator training programmes have their roots in the Language Institutes: those in Tampere University and in the universities of Eastern Finland, Helsinki and Turku. The idea to write the history of these programmes was born amidst celebrations of their 50th anniversaries, falling within a 5-year span between 2016 and 2021. The present thematic issue is the outcome of the history work started during those years, and with contributions presenting different aspects of translator training in Finland: the establishment of the first translator training institutes; the early theoretical thinking behind the translation pedagogy of one of the first trainers, Atso Vuoristo; a systematic review of Finnish doctoral dissertations in Translation Studies; and students' and teachers' reflections and memories of their time working and studying in these institutions. Acknowledging the fact that there is much more ground to cover, we conclude this article by suggesting future avenues for research on this
topic.